Determination of polycyclic aromatic hydrocarbons in water using dispersive liquid-liquid microextraction-gas chromatography-mass spectrometric - Imrigha, Nada Abusalah; Sanagi , Mohd Marsin; Sharef , Sarra Younes (Journal of Pure & Applied Sciences, 2022)
For the extraction of polycyclic aromatic hydrocarbons (PAHs) from water samples, a new sample preparation approach based on dispersive liquid-liquid microextraction (DLLME) was developed. In this procedure, a water sample was injected with a mixture of carbon tetrachloride, CCl4 (extraction solvent), and acetone (disperser solvent) to generate an emulsion in which the PAHs were extracted into fine droplets of extraction solvent. The impacts of several extraction parameters were explored, including extraction solvent type, disperser solvent type, extraction solvent volume, and disperser solvent volume. For phenanthrene and fluoranthene, the calibration curve correlation coefficient (r2) was 0.9993 and 0.9973, respectively. For phenanthrene and fluoranthene, the limits of detection (LODs) were 0.0008 g/mL and 0.0006 g/mL, respectively. For phenanthrene and fluoranthene, the relative standard deviations (RSDs) were 10.69 percent and 9.72 percent, respectively. The analyte recovery rates ranged from 100.5 to 107.8%. Phenanthrene and fluoranthene were discovered in the samples.